Facile Synthesis of Novel Polyethylene‐Based A‐B‐C Block Copolymers Containing Poly(methyl methacrylate) Using a Living Polymerization System. Issue 3 (7th December 2015) - Song, Xiangyang; Ma, Qiong; Cai, Zhengguo; Tanaka, Ryo; Shiono, Takeshi; Grubbs, Robert B.
Abstract : Ethylene–propylene–methyl methacrylate (MMA) and ethylene–hexene–MMA A‐B‐C block copolymers with high molecular weight (>100 000) are synthesized using fluorenylamide‐ligated titanium complex activated by modified methylaluminoxane and 2, 6‐ di ‐ tert ‐butyl‐4‐methylphenol for the first time. After diblock copolymerization of olefin is conducted completely, MMA is added and activated by aluminum Lewis acid to promote anionic polymerization. The length of polyolefin and poly (methyl methacrylate) (PMMA) is controllable precisely by the change of the additive amount of olefin and polymerization time, respectively. A soft amorphous polypropylene or polyhexene segment is located between two hard segments of semicrystalline polyethylene and glassy PMMA blocks. Abstract : The synthesis of A‐B‐C block copolymers consisting of both hard segments of semicrystalline polyethylene and glassy poly (methyl methacrylate) and soft amorphous segment of polypropylene or polyhexene is achieved using the fluorenylamide‐ligated titanium complex for the first time.